Improved determination of the β-[nu][bar]e angular correlation coefficient a in free neutron decay with the aSPECT spectrometer - Beck, Marcus; Schmidt, Ulrich (Physical review, 2020)
We report on a precise measurement of the electron-antineutrino angular correlation (a coefficient) in free neutron beta decay from the aSPECT experiment. The a coefficient is inferred from the recoil energy spectrum of the protons which are detected in 4π by the aSPECT spectrometer using magnetic adiabatic collimation with an electrostatic filter. Data are presented from a 100-day run at the Institut Laue Langevin in 2013. The sources of systematic errors are considered and included in the final result. We obtain a=−0.10430(84) which is the most precise measurement of the neutron a coefficient to date. From this, the ratio of axial vector to vector coupling constants is derived giving |λ|=1.2677(28).
Im Titel ist "nu" als griechischer Buchstabe dargestellt
Im Titel steht der griechische Buchstabe "nu" mit einem Oberstrich
Im Titel ist der Buchstabe e tiefgestellt
Gesehen am 17.09.2020